1984
DOI: 10.1007/bf01728180
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral effects of thyroid hormones: Alteration of intracellular Na-concentration, ouabain-sensitive Na-transport, and Na-Li countertransport in human red blood cells

Abstract: To investigate the effect of thyroid hormones on erythrocyte cation transport systems and intracellular electrolyte content we have measured the activity of Na-K ATPase, Na-Li countertransport, as well as red cell sodium and potassium contents in patients with hyperthyroidism and in euthyroid controls. Intracellular Na- and K-concentrations were determined in erythrocytes washed three times in isotonic MgCl2 solution. Ouabain-sensitive Na-transport was estimated as the increase of Na before and after addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
3
1
1
Order By: Relevance
“…In hyperthyroidism it has been suggested that (1) the increase in membrane permeability (Rubython et al, 1983), (2) change in lipid composition of the membrane (Cole & Waddell, 1976), or (3) elevated protein catabolism is responsible for decreased Na + ,K + -ATPase activity in hyperthyroidism. In contrast, elevated Na + ,K + -ATPase activity was reported by Sutterlin et al (1984) and Yoon et al (1989). Our findings indicate that the pump activity may be decreased due to enhanced freeradical-induced membrane damage.…”
Section: Discussioncontrasting
confidence: 79%
“…In hyperthyroidism it has been suggested that (1) the increase in membrane permeability (Rubython et al, 1983), (2) change in lipid composition of the membrane (Cole & Waddell, 1976), or (3) elevated protein catabolism is responsible for decreased Na + ,K + -ATPase activity in hyperthyroidism. In contrast, elevated Na + ,K + -ATPase activity was reported by Sutterlin et al (1984) and Yoon et al (1989). Our findings indicate that the pump activity may be decreased due to enhanced freeradical-induced membrane damage.…”
Section: Discussioncontrasting
confidence: 79%
“…With regard to the thyroid function, erythrocyte LSC activity was significantly lower in patients with low TSH level among a group of lithium-treated bipolar patients [15]. In the same line the excess of thyroid hormones in hyperthyroidical patients has been suggested [18] to be responsible for the depression of the LSC and consequently for an increase of the LR.…”
Section: Interrelations Between Lithium Therapy Auto-immune Thyroidimentioning
confidence: 84%
“…Sutterlin ve ark. ise eritrosit memranı Na-K ATPaz aktiviteside artış olduğunu gözlemlemiştir 42 . Yapılan çalışmalarda tiroid hormonlarının etkisiyle kırmızı hücre filtrelenebilirliğinde açıkça bir azalma meydana geldiği ortaya konulmaktadır.…”
Section: Hipertiroidi-hipotiroidiunclassified